Spectrum of conditionally pathogenic microflora isolated from the prostate secret in chronic bacterial prostatitis patients - T. V. Tunik; E. I. Ivanova; E. V. Grigorova; N. M. Voropayeva; V. A. Vishnevskaya (Acta Biomedica Scientifica)
The article represents a description for microbiocenosis of isolated prostate secret. The initial samples were taken on the territory of the Irkutsk region from men diagnosed with chronic bacterial prostatitis in the acute stage. 90 % of samples of isolated prostate secret were tested by cultural method revealed 4l representatives of opportunistic pathogenic microflora. Gram-positive microorganisms were found in most samples (86.7 %). Staphylococcus genus representatives formed the majority in isolated samples of conditionally pathogenic microflora (66.7 %). As for gram-negative representatives (which role in chronic bacterial prostatitis is proven by multiple research), E. coli and K. pneumoniae were isolated. In the half of samples, we revealed bacterial associations consisting mostly of two kinds of microorganisms. Staphylococcus epidermidis was isolated in 70 % of such associations.